Odpowiedzi

2010-01-13T15:17:07+01:00
A). -2x+1-3x-1=-5x
b).4a-7b-2a-3b=2a-10b
c).2p-r+2r-p= p+r
d).x+y+x-z+z-y=2x
2010-01-13T15:17:46+01:00
A.) -(2x-1)-(3x+1)=-2x+1-3x-1=-5x
b.) (4a-7b)-(2a+3b)=4a-7b-2a-3b=2a-10b
c.) (2p-r)+(2r-p)= 2p-r+2r-p= p+r
d.) (x+y)+(x-z)+(z-y)= x+y+x-z+z-y= 2x


Nie wiem czy to bobrze. Chyba coś takiego:P
1 5 1
2010-01-13T15:18:22+01:00
A.) -(2x-1)-(3x+1)=-2x+1-3x-1=-5x
b.) (4a-7b)-(2a+3b)=4a-7b-2a-3b=2a-10b
c.) (2p-r)+(2r-p)=2p-r+2r-p=p+r
d.) (x+y)+(x-z)+(z-y)=x+y+x-z+z-y=2x